2017
DOI: 10.3390/su9050731
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Window Films on the Overall Energy Consumption of Existing UK Hotel Buildings

Abstract: Abstract:Recently, considerable attention has justifiably been directed towards energy savings in buildings as they account for up to 20-40% of total energy consumption in developed countries. In the United Kingdom, studies have revealed that buildings' CO 2 emissions for account for at least 43% of total emissions. Window panels are a major component of the building fabric with considerable influence on the façade energy performance and are accountable for up to 60% of a building's overall energy loss. Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…TAS is designed by the Engineering Development Solutions Limited (Milton Keynes, UK) and comprises different modules such as 3D Modeller, Building Simulator, Systems, etc., that simulate the thermal performance of the building and estimate the building's energy consumption. TAS provides the opportunity to combine the dynamic thermal simulation of the building with control functions over natural and mixed mode ventilations [13]. A detailed description about the software and its capabilities can be found in [30,31].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…TAS is designed by the Engineering Development Solutions Limited (Milton Keynes, UK) and comprises different modules such as 3D Modeller, Building Simulator, Systems, etc., that simulate the thermal performance of the building and estimate the building's energy consumption. TAS provides the opportunity to combine the dynamic thermal simulation of the building with control functions over natural and mixed mode ventilations [13]. A detailed description about the software and its capabilities can be found in [30,31].…”
Section: Methodsmentioning
confidence: 99%
“…The building façade is mostly covered in curtain wall with a double-glazed unit comprising two 4 mm clear panes with a 50 mm air-filled gap. As the building was built in 2009, it complies with the 2006 UK building regulation [13]. The building is sealed and fully air conditioned.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The UK government has justifiably put considerable focus towards reducing the CO 2 emissions from buildings (residential and commercial) because studies/analyses have shown that they account for at least 43% [7,8]. To achieve the CO 2 emissions reduction, it is important to significantly reduce emissions from existing buildings which makes up the bulk of buildings during this period, especially commercial ones such as hotels which accounts for one of the top sectors [9].…”
Section: Introductionmentioning
confidence: 99%